2015
DOI: 10.1038/nn.3976
|View full text |Cite
|
Sign up to set email alerts
|

Role of Tet1 and 5-hydroxymethylcytosine in cocaine action

Abstract: TET enzymes mediate the conversion of 5-methylcytosine (5mC) to 5-hydroxymethylcytosine (5hmC), which is enriched in brain, and its ultimate demethylation. However, the influence of TET and 5hmC on gene transcription in brain remains elusive. We demonstrate that TET1 is downregulated in nucleus accumbens (NAc), a key brain reward structure, by repeated cocaine administration, which enhances behavioral responses to cocaine. We then identify 5hmC induction in both putative enhancers and coding regions of genes t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
158
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(174 citation statements)
references
References 75 publications
14
158
1
1
Order By: Relevance
“…TET1 has been demonstrated to be down-regulated in response to cocaine administration, leading to locus-specific decreases in 5-hmc. 39 Whilst other studies have reported no change in global 5-hmc content in response to heroin and cocaine exposure 19,20,39 , they have focussed upon a single region (nucleus accumbens) or utilized homogenized brain tissue and therefore could not exclude the possibility of localized changes in 5-hmc in specific regions of the brain. The limitations of such approaches were addressed in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…TET1 has been demonstrated to be down-regulated in response to cocaine administration, leading to locus-specific decreases in 5-hmc. 39 Whilst other studies have reported no change in global 5-hmc content in response to heroin and cocaine exposure 19,20,39 , they have focussed upon a single region (nucleus accumbens) or utilized homogenized brain tissue and therefore could not exclude the possibility of localized changes in 5-hmc in specific regions of the brain. The limitations of such approaches were addressed in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Here we show that compulsive METH taking is associated with large-scale changes in DNA hydroxymethylation in the rat NAc, consistent with a potential role for DNA hydroxymethylation processes in addiction. 43 Genes that were affected in the METH-addicted rats included those that participate in calcium signaling, among others. In contrast, nonaddicted rats exhibited increased expression of mRNAs that code for several K+ channels in NAc, but not in the PFC and dorsal striatum.…”
Section: Hypo-hydroxymethylated Peaks (394 Peaks)mentioning
confidence: 99%
“…Previous studies have demonstrated that 5hmC correlates positively with gene expression in neurons of the CNS and in olfactory neurons (Khare et al 2012; Colquitt et al 2013; Perera et al 2015), and that some neurological disease states show dynamic regulation of 5hmC (Feng et al 2015). Microarray and RNA sequencing (RNA-Seq) experiments in animal models of neuropathic pain have shown that hundreds of genes are dynamically upregulated by injury and that such changes contribute to the development of neuropathic pain (Costigan et al 2002; Scholz and Woolf 2007; LaCroix-Fralish et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…One novel epi-genetic mark that has been intensely studied in the central nervous system (CNS) is 5-hydroxymethylcytosine (5hmC), which is produced by hydroxylation of 5-methylcytosine (5mC) through the action of the Ten-eleven translocation hydroxylases (TET1–3) (Pastor et al 2013). 5hmC has been implicated in many neuronal processes, including learning, memory, synaptic transmission, and disease states such as cocaine addiction (Szulwach et al 2011; Kaas et al 2013; Feng et al 2015). Genome-wide studies have revealed that 5hmC correlates positively with gene expression in neurons, in contrast to its progenitor, 5mC, which generally acts to silence gene expression (Xu et al 2011; Denk and McMahon 2012; Colquitt et al 2013).…”
Section: Introductionmentioning
confidence: 99%